2012
DOI: 10.1002/ibd.21676
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxanthine guanine phosphoribosyltransferase activity is related to 6-thioguanine nucleotide concentrations and thiopurine-induced leukopenia in the treatment of inflammatory bowel disease

Abstract: High levels of HPRT activity could be a predictor of leukopenia and unsafe 6-TGN concentrations in patients undergoing AZA/6-MP therapy. This could partly explain the therapeutic response or toxicity that could not be adequately explained by the polymorphisms of TPMT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 65 publications
0
35
0
Order By: Relevance
“…No case with TPMT mutation was found in our study. Therefore, other genetic and epigenetic factors must play a role in the incidence of the ADRs, including ITPA (21), hypoxanthine guanine phosphoribosyltransferase (HPRT) (22), and GST (6).…”
Section: Discussionmentioning
confidence: 99%
“…No case with TPMT mutation was found in our study. Therefore, other genetic and epigenetic factors must play a role in the incidence of the ADRs, including ITPA (21), hypoxanthine guanine phosphoribosyltransferase (HPRT) (22), and GST (6).…”
Section: Discussionmentioning
confidence: 99%
“…[16] Safety monitoring by regular blood counts is therefore essential, specifically in patients with this combination therapy, as they have an increased risk of developing myelotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…25 Ding and colleagues recently reported a correlation between the activity of HGPRT and 6-TGN concentrations, which was not observed in this study possibly due the small sample size. 31 Nonetheless, the enhanced HGPRT activity may at least in part explain the rise in 6-TGN concentrations as HGPRT is the first enzyme, responsible for the generation of 6-TGN. Since HGPRT is also involved in formation of methylated 6-MP ribonucleotides, one would expect an increase in 6-MMPR.…”
Section: 29mentioning
confidence: 99%
“…In analogy with a previous study no difference in HGPRT activity was observed between gender and disease type (CD and UC). 31 As a classical XO inhibitor, allopurinol decreased the activity of XO after initiating allopurinol. With regard to thiopurine metabolism, decreased XO activity, either by inhibition or by a decreased activity of XO, causes less shunting towards the XO pathway, thereby increasing the concentration of 6MP that remains available for conversion into 6-TGN but theoretically also for the conversion into 6-MMPR (Fig.…”
Section: 29mentioning
confidence: 99%